2015
DOI: 10.1002/bip.22659
|View full text |Cite
|
Sign up to set email alerts
|

Peptide splicing in a double‐sequence analogue of trypsin inhibitor SFTI‐1 substituted in the P1 positions by peptoid monomers

Abstract: Recently, we described a process of trypsin-assisted peptide splicing of analogs of trypsin inhibitor SFTI-1, that seems to be very similar to proteasome-catalyzed peptide splicing. Here, we show, for the first time, that a peptide-peptoid hybrid (peptomer) can also be spliced by trypsin. Incubation of a double sequence SFTI-1 analog, containing two peptoid monomers, with equimolar amount of trypsin leads to formation of monocyclic peptomer as the main product. We proved that the peptide bond formed by a pepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The Narg residue has a guanidyl‐containing side chain shifted from α ‐carbon into α ‐nitrogen atom. In our previous reports we showed that a peptide bond formed between carboxyl group of an N ‐substituted glycine residue and an amino group proteinogenic amino acid residue is either completely or apparently more resistant to proteolytic degradation, compared to a common peptide bond between two amino acids. Narg was introduced in the position 2 since we found that the bond between Arg2 and Cys3 in peptide I was hydrolyzed by proteasome in the SDS‐containing buffer.…”
Section: Resultsmentioning
confidence: 96%
“…The Narg residue has a guanidyl‐containing side chain shifted from α ‐carbon into α ‐nitrogen atom. In our previous reports we showed that a peptide bond formed between carboxyl group of an N ‐substituted glycine residue and an amino group proteinogenic amino acid residue is either completely or apparently more resistant to proteolytic degradation, compared to a common peptide bond between two amino acids. Narg was introduced in the position 2 since we found that the bond between Arg2 and Cys3 in peptide I was hydrolyzed by proteasome in the SDS‐containing buffer.…”
Section: Resultsmentioning
confidence: 96%